Estudo da viabilidade econômica para produção de biogás gerado nas estações de tratamento de esgoto no município de Poços de Caldas - Reis, João Marcos Dos (2021)
Recently, there has been a growing concern of the world population regarding sustainable development alternatives. Thus, the treatment and reuse of effluents have gained prominence in scientific research. Therefore, reducing environmental impacts, solutions associated with the scarcity of water resources, and energy production (biogas) as an alternative to fossil fuels. The objective of this work was to evaluate the potential of methane production and energy generation in the sewage treatment in the city of Poços de Caldas (MG) Brazil, comparing the economic indicators of the cost of implementing an energy generation plant in these establishments. For the present study, 3 ETEs (Córrego D'Antas, Contorno and Bortolan) were selected. The Córrego D’antas and Contorno have a UASB reactor, while Bortolan is composed of a compact system, where the aerobic and anaerobic parts occur in the same reactor. The influent and effluent samples were characterized in the laboratories of DMAE (ETE 1) and Qualin Serviços LTDA (ETE 2 and 3). The parameters evaluated, using the Probio 1.0 software, were the production of biogas and its energy potential, technical-economic analysis of the costs of implementing a power generation plant, investment and operation costs, energy analysis, and economic feasibility. Probio 1.0 software considers all possible COD conversion routes and their losses, estimating conservative, optimistic, and typical scenarios. ETE 1 (Córrego D'Antas) has a higher flow and COD load than the others. All ETEs presented proportions above 60% of CH4 in the biogas. However, ETE 3 (Bortolan) did not have the minimum amount of biogas production to allow the installation of an energy generation plant. Regarding investment costs, ETE 1 has a total annual cost of R$70,467.96, while ETE 2 has a value of R$31,967.38. The energy analysis showed that ETE 1 has a monthly production capacity higher than ETE 2, with values of 165,000 kWh/month and 14,625 kWh/month, respectively. Regarding the return on investment (Payback), ETE 1 requires 25 months, while ETE 2 would need 221 months. Therefore, it is concluded that only ETE 1 is viable for installing a power plant from biogas generated by sewage treatment, considering its energy production capacity and the return-on-investment time.